Co-option of Plasmodium falciparum PP1 for egress from host erythrocytes - Aditya S. Paul (Nature Portfolio, 2020)
Plasmodium protein phosphatase PP1 is essential for the asexual proliferation of malaria parasites. Here the authors show that PP1 regulates egress of parasites from host red blood cells, integrating parasite intrinsic pathways with environmental signals for release into the bloodstream.